Efektifitas pijat punggung menggunakan minyak esensial lavender terhadap produksi asi ibu pasca salin - Wahida Yuliana; Mohammad Hakimi; Yuli Isnaeni (Universitas Aisyiyah Yogyakarta, 2016)
This study aims to determine the effect of back massage using lavender essensial oils toward milk production of postpartum mother at Community Health Center of Yogyakarta city. The design ofthe study wasQuasiexperimentwithpost testonlynonequivalentcontrolgroupdesign.Thesampling technique isconsecutive sampling.There is 30 respondents for each group. The analysis used waschi-square test. The analysis results showed the treatment ofback massageusinglavenderis RR 3,33, it means thatit has chanceof 3,33times toincrease milk productionaftermassasecontrolled bytreatment, parity, BMI andfrequency of breastfeeding. The fifth modelis the bestmodelbecause it is ableto explainthe breastmilk productionby 26%.